Risk assessment of Artemia egg shell-Mg-P composites as a slow-release phosphorus fertilizer during its formation and application in typical heavy metals contaminated environment. (1st March 2023) - Wang, Sufeng; Lv, Xiaojuan; Fu, Mingwei; Wang, Zijing; Zhang, Dan; Sun, Qina
Abstract: Artemia egg shell loaded with nano-magnesium (shell-Mg) can be used to recover phosphorus from wastewater. The exhausted Artemia egg shell-Mg (denoted as shell-Mg-P) can be used as a slow-release fertilizer for phosphorus reuse. However, due to the coexistence of heavy metal ions in the environment, the application of slow-release fertilizer for phosphorus removal and reuse may have potential risks. In this paper, the potential risks of Pb 2+, Cd 2+, Zn 2+ and Cu 2+ in phosphorus wastewater and soil were studied from the formation and application process of shell-Mg-P. The result showed that shell-Mg adsorbed Pb 2+, Cd 2+, Zn 2+ and Cu 2+ in phosphate wastewater during the formation of shell-Mg-P and became shell-Mg-P-metal hybrid biomaterial. Although the experiment proved that the existence of heavy metal ions did not affect the phosphorus slow-release behavior of slow-release fertilizer, but the heavy metal ions in the shell-Mg-P-metal were also slow released. The pot experiment results confirmed that the slow-release phosphorus fertilizers (shell-Mg-P and shell-Mg-P-metal) in the soil polluted in low concentration of heavy metals can reduce the amount of heavy metals in whole wheat seedlings and promote wheat seedling growth. However, the application of slow-release fertilizers increased the translocation efficiency (TFR to SL ) of metal from root (R) to aboveground part (stem and leaves, SL), promoted the transportation of heavy metals from roots to the stems and leaves, and increased the safety risk of the wheat seedling edible. Therefore, besides the positive role of slow-release fertilizers in retaining heavy metals and reducing the amount of heavy metals in whole seedlings, the risk that it may aggravate the translocation of heavy metals to stems and leaves should be paid more attention, so as to ensure the safe and reliable application of slow-release fertilizers. Graphical abstract: Image 1 Highlights: A slow-release phosphorus fertilizer in the soil polluted in low concentration of heavy metals can reduce the amount of heavy metals in whole wheat seedlings. A slow-release phosphorus fertilizer in the soil polluted in low concentration of heavy metals can promote wheat seedling growth. The application of slow-release fertilizers increased the translocation efficiency of metal from root to aboveground part. The application of slow-release fertilizer promote the transportation of heavy metals from roots to the stems and leaves. The application of slow-release fertilizer increase the safety risk of the wheat seedling edible.